An Application of ASP Theories of Intentions to Understanding Restaurant Scenarios: Insights and Narrative Corpus. Issue 2 (22nd March 2020) - ZHANG, QINGLIN; BENTON, CHRIS; INCLEZAN, DANIELA
Abstract: This paper presents a practical application of Answer Set Programming to the understanding of narratives about restaurants. While this task was investigated in depth by Erik Mueller, exceptional scenarios remained a serious challenge for his script-based story comprehension system. We present a methodology that remedies this issue by modeling characters in a restaurant episode as intentional agents . We focus especially on the refinement of certain components of this methodology in order to increase coverage and performance. We present a restaurant story corpus that we created to design and evaluate our methodology.